2012
DOI: 10.1517/14656566.2012.699523
|View full text |Cite
|
Sign up to set email alerts
|

Off-label uses of trazodone: a review

Abstract: Few clinical trials have been conducted to evaluate trazodone's efficacy in the treatment of the diseases and symptoms for which it is often used in clinical practice. More studies are necessary to investigate possible new therapeutic indications, and to scientifically demonstrate the risk/benefit ratio for the many conditions for which trazodone is used, but not approved by the FDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 70 publications
0
44
0
2
Order By: Relevance
“…14 For humans, there are various indications for administration of trazodone including treatment of depression, anxiety disorders, insomnia, certain causes of pain, and cognitive dysfunction. 15 In dogs, however, reported 3 clinical use of trazodone is limited to chronic management of behavioral disorders, including storm phobias and separation anxiety, and it is typically administered in combination with conventional psychoactive medications. Its broad spectrum of pharmacological action and clinical applications in humans suggests that trazodone may have similar versatility for treatment of companion animals.…”
Section: Discussionmentioning
confidence: 99%
“…14 For humans, there are various indications for administration of trazodone including treatment of depression, anxiety disorders, insomnia, certain causes of pain, and cognitive dysfunction. 15 In dogs, however, reported 3 clinical use of trazodone is limited to chronic management of behavioral disorders, including storm phobias and separation anxiety, and it is typically administered in combination with conventional psychoactive medications. Its broad spectrum of pharmacological action and clinical applications in humans suggests that trazodone may have similar versatility for treatment of companion animals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the majority of the prescriptions in the absence of psychiatric diagnoses of MDD and anxiety disorders in this study were likely for mental health complaints that did not meet the criteria for these disorders. While there is some evidence supporting the efficacy of ADs for sub-syndromal depressive symptoms and dysthymic disorder, 25, 26 and for off-label use of ADs in the treatment of sleep disorders, 27 these uses are controversial. 28, 29 …”
Section: Discussionmentioning
confidence: 99%
“…Neither has been proven to be effective for RLS/WED. While there is some evidence for use of trazodone to treat insomnia in depression, there is limited evidence for the treatment of insomnia in the non-depressed population, although such use is common in clinical practice [183][184][185]. A small study found limited efficacy of clonidine for RLS/WED [186].…”
Section: Other Medicationsmentioning
confidence: 99%